Ce que les mondes parallèles font au personnage de série télévisée : une esthétique du character overhaul - Pablo Cabeza-Macuso (ReS Futurae)
This article questions the status of the sci-fi television series character when confronted with his double from a parallel world. The character is analyzed as dependent on narrative structures, the fictional world, aesthetic forms, as well as the practices of the actors. The figurative analyzes deployed in this article seek to account for the various aesthetics surrounding the relations to otherness experienced by split serial characters. The analysis start with doubles easily recognizables (by caricature, bodily alienation, and the “framing” of the alterity) and continue with overhauls increasingly imperceptibles (by intrication, entanglement, and “double-sided” image).